Retrospective analysis of children with 46,XX testicular/ovotesticular DSD: a 10-year single-center experience - Yan Gong; Xiaoqin Yin; Jing Xu; Yan Li; Qingxu Liu; Shasha Zhou; Fei Wang; Yiqing Lyu; Sheng Guo; Wenyan Huang; Pin Li (Frontiers in Endocrinology)
Purpose46,XX testicular/ovotesticular differences/disorders of sexual development (TDSD/OTDSD) are rare in childhood and exhibit marked distinctions compared to those in adulthood. This study aimed to summarize the clinical characteristics and outcomes of 46,XX TDSD/OTDSD in childhood.MethodsThe sexual development characteristics, hormone profiles, chromosomal analysis, fluorescence in situ hybridization analysis (FISH) sex-determining region Y (SRY) analysis (peripheral blood and tissues), molecular genetic etiology, gonadal pathology, risk of gonadal tumors, and assigned gender of 52 patients were collected and analyzed.ResultsThe median age at initial presentation was 18 months, and external masculinization score(EMS) within the range of 3 < EMS ≤ 6 was more prevalent. There were no statistical differences in hormone levels [luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone (T)] between the different age groups. Among the 52 children, 4 showed positive SRY in peripheral blood, whereas none of the 8 children exhibited positive SRY in tissue samples. A total of 29 children underwent whole exome sequencing (WES) and copy number variant (CNV) analysis, but no genetic variants were identified. A total of 47 children underwent gonadal biopsy and showed no evidence of tumors. However, immunohistochemical analysis revealed that 2 of 16 children were OCT3/4 positive. The most frequent type of gonadal pathology (17/47) was bilateral seminiferous tubules. After the assessment, gender assignment was revised in six cases: five individuals originally assigned as female at birth were reassigned as male, while one individual assigned as male was changed to female. In seven cases, the gender of rearing remained undetermined pending further longitudinal psychosocial assessment. Among the female-reared cohort, three children were more than 11 years old. As a result of undergoing bilateral gonadectomy at an early age, the patients were unable to spontaneously enter puberty. However, given their short stature, they are receiving growth hormone (GH) treatment and have not yet received sufficient sex hormone replacement therapy (HRT). Among the male-reared cohort, seven children had entered puberty. The average age at puberty onset was 12 ± 0.87 years, the average testicular volume was 5.14 ± 1.57 mL, the mean basal LH level was 6.44 ± 4.19 IU/L, the mean basal FSH level was 13.18 ± 10.22 IU/L, and the mean basal T was 3.40 ± 1.63 nmol/L.ConclusionCompared to adults, children with 46,XX testicular/ovotesticular DSD were very different. SRY-negative children were predominant and tended to have more severe external genital abnormalities during childhood. Peripheral blood or tissue SRY mosaicism was not a prevalent cause and the intricate genetic pathways behind these cases were unknown. There were no statistical differences in hormone levels (LH, FSH, and T) between the different age groups. The assigned gender is mainly male, and the incidence of gonadal tumor risk markers was modest. During adolescence, their testosterone levels could normalize despite elevated FSH and LH levels.